Update on Emerging Treatment Options for Primary Biliary Cholangitis - Aguilar MT (Dove Medical Press, 2020)
Maria T Aguilar,1 David M Chascsa2 1Department of Gastroenterology & Hepatology, Mayo Clinic, Scottsdale, AZ, USA; 2Department of Gastroenterology & Hepatology, Mayo Clinic, Phoenix, AZ, USACorrespondence: Maria T Aguilar Email aguilar.maria1@mayo.eduAbstract: Primary biliary cholangitis (PBC) is a rare autoimmune cholestatic liver disease that may progress to fibrosis or cirrhosis. Treatment options are currently limited. Ursodeoxycholic acid (UDCA) remains first-line therapy and has been proven to normalize serum biochemistries, halt histologic disease progression, and lead to patient survival comparable to the general population. Obeticholic acid (OCA) was recently approved as adjunct therapy in PBC patients with inadequate response or intolerance to UDCA. However, OCA has been associated with worsening pruritus in clinical studies which may limit its use in this patient population. Several studies are currently underway to address the lack of treatment options for PBC. Of these, fibrates, which have been used in Japan for over a decade, have produced promising results. Furthermore, as currently approved therapies for PBC do not address the potentially debilitating clinical symptoms of PBC such as pruritus and fatigue, supplemental therapy is often required for symptom control.Keywords: primary biliary cholangitis, obeticholic acid, fibrate